Multi-dimensional genomic analysis of myoepithelial carcinoma identifies prevalent oncogenic gene fusions - Martin G. Dalin (Nature Portfolio, 2017)
Myoepithelial carcinoma (MECA) is a rare aggressive salivary gland cancer. Here, the authors analyze the genomic landscape of MECA and identify a high prevalence of oncogenic gene fusions, primarily PLAG1 fusions, highlighting TGFBR3-PLAG1 as a potential hallmark of MECA.